Technology life cycle and S curves applied to byproducts of the fish farming industry [Ciclo de vida de tecnologías y curvas en S aplicadas en subproductos de la agroindustria piscícola] (2017)
The life cycle of available technologies through the S-curves method on three technologies is analyzed: hydrolyzed protein, animal feeding and probiotics, related to products of the fish industry. For this, strategies were constructed to search articles and patents in specialized databases such as Scopus and Free patents online. For the analysis of the information, S curves were used for calculating the inflection point. This determines the state of technology within its life cycle and helps decision making regarding the right time to exercise mechanisms of intellectual property and technology law, and suggest strategies of monitoring and investment. Among the most important results it is observed that in articles, two of the technologies discussed, hydrolyzed protein and probiotics have not reached their turning point, and the same happened with patent for animal feeding. However, the technology of hydrolyzed protein, from the point of view of the articles, will enter its phase of maturity and decline after 2016.